Developing issue-based teaching materials to improve student learning outcomes in Freshwater Biology course - Kamaludin, Syaris; Surtikanti, Hertien Koosbandiah; Surakusumah, Wahyu (University of Muhammadiyah Malang, 2018)
One of Freshwater Biology course problems is that the students were unable to understand the environmental phenomena around them. The aim of this study was to develop issue-based teaching materials in Freshwater Biology course to improve the studentsâ understanding about the environmental phenomena through their learning outcomes. This research and development used three phases of the 4D model developed by Thiagarajan, namely define, design, and development. The development results were validated by content and media experts. The design used for pilot test, which was conducted among 20 students, was one group pretest-posttest design; meanwhile the data analysis technique used was independent t-test. It can be concluded that the teaching materials developed was valid with the average validation score as high as 79.83%. In addition, there was significant improvement (sig. 0.000) of student learning outcomes after attending the course which implementing the issue-based teaching materials developed. Thus, the implementation of issue-based teaching materials is recommended in Freshwater Biology course due to its potential in improving studentsâ learning outcomes.